2014
DOI: 10.1186/s12989-014-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based genotoxicity screening of metal oxide nanoparticles using the ToxTracker panel of reporter cell lines

Abstract: BackgroundThe rapid expansion of manufacturing and use of nano-sized materials fuels the demand for fast and reliable assays to identify their potential hazardous properties and underlying mechanisms. The ToxTracker assay is a recently developed mechanism-based reporter assay based on mouse embryonic stem (mES) cells that uses GFP-tagged biomarkers for detection of DNA damage, oxidative stress and general cellular stress upon exposure. Here, we evaluated the ability of the ToxTracker assay to identify the haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 46 publications
(67 reference statements)
7
78
0
Order By: Relevance
“…Thus, the results from our study suggested that the oxidative stress responses to AgNPs could be explained by the released Ag + ions from the nanoparticles. Our results were in agreement with other studies in which the stress response indicated by gene expression profile following AgNPs exposure was induced by the released Ag + ions (Prasad et al, 2013;Karlsson et al, 2014). For equal mass of AgNPs with different sizes, the smaller particles will be greater in number and have higher total surface area, thus probably contributing to the more toxic potential observed with smaller AgNPs (Prasad et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, the results from our study suggested that the oxidative stress responses to AgNPs could be explained by the released Ag + ions from the nanoparticles. Our results were in agreement with other studies in which the stress response indicated by gene expression profile following AgNPs exposure was induced by the released Ag + ions (Prasad et al, 2013;Karlsson et al, 2014). For equal mass of AgNPs with different sizes, the smaller particles will be greater in number and have higher total surface area, thus probably contributing to the more toxic potential observed with smaller AgNPs (Prasad et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…The luciferase activity induced by AgNPs were generally in accordance with the oxidative damage indicated by MDA concentration, ROS level and GSH depletion, and the Ag + ions release in cell medium. Compared with the other three luciferase reporter cells in this study or other reporter system reported for detecting the oxidative stress (Prasad et al, 2013;Karlsson et al, 2014), the HSPA1A promoter in HepG2-luciferase cells is generally more sensitive to nanoparticles. The HepG2 cells, derived from a human liver hepatoma, are reported to retain many properties of primary cells such as containing many functional phase-Ι and-II enzymes which are lost in most cultured cell lines (Doostdar et al, 1993;Westerink and Schoonen, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…In vitro studies have shown that ZnO is cytotoxic at relatively low concentrations as compared to other types of engineered nanomaterials such as titanium dioxide, carbon nanotubes [7][8][9][10] . Similar findings on cytotoxicity have been observed in broncho-alveolar lavage cells after pulmonary exposure to ZnO NP, which has been attributed to the dissolution of Zn ions [11;12] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some reports showed that ENMs increase γ-H2AX levels in in vitro experiments (102105). Metal-oxide NPs in particular, such as CuO, ZnO and NiO, etc., induced the formation of γ-H2AX foci (102,104).…”
Section: Introductionmentioning
confidence: 99%